The peregrine profession : transnational mobility of Nordic engineers and architects, 1880-1930 - Grönberg, Per-Olof (Studies in global social history, 2019)
In The Peregrine Profession Per-Olof Groenberg offers an account of the pre-1930 transnational mobility of engineers and architects educated in the Nordic countries 1880-1919. Outlining a system where learning mobility was more important than labour market mobility, the author shows that more than every second graduate went abroad. Transnational mobility was stronger from Finland and Norway than from Denmark and Sweden, partly because of slower industrialisation and deficiencies in the domestic technical education. This mobility included all parts of the world but concentrated on the leading industrial countries in German speaking Europe and North America. Significant majorities returned and became agents of technology transfer and technical change. Thereby, these mobile graduates also became important for Nordic industrialisation.